Esthetic Evaluation of Implants Placed after Orthodontic Treatment in Patients with Congenitally Missing Lateral Incisors. Issue 1 (17th December 2013) - Mangano, Carlo; Levrini, Luca; Mangano, Alessandro; Mangano, Francesco; Macchi, Aldo; Caprioglio, Alberto
Abstract Objective The aim of this retrospective study was to evaluate the esthetic outcome of single tooth Morse taper connection implants used to replace congenitally missing lateral incisors after orthodontic treatment by means of the pink esthetic score (PES) and white esthetic score (WES) index. Materials and Methods Twenty consecutive patients who were treated with a single tooth Morse taper connection implants (Leone Implant System®, Florence, Italy) were enrolled in this study. An independent calibrated examiner applied the PES/WES index to 20 implant‐supported restorations 3 months and 3 years after implant placement. Results No implants were lost. All 20 implants fulfilled the established success criteria for dental implants with regard to osseointegration and prosthetic complications, with an overall implant‐crown success of 100.0%. At the 3 year examination, the mean distance between the implant shoulder and the first visible bone‐implant contact was of 0.49 ± 0.18 mm (95% confidence interval 0.41–0.57); the mean PES was 8.15 ± 1.69, and the mean WES was 8.70 ± 0.92. Conclusions The placement of single‐tooth Morse taper connection implants for rehabilitation of congenitally missing lateral incisors after orthodontic treatment represents a successful procedure in the medium term. Further studies are necessary in order to assess the long‐term esthetic score. Clinical Significance This paper evaluates the esthetic outcome of Morse taper connection implants placed to restore congenitally missing lateral incisors after orthodontic treatment.